Influence of particle size and shape properties on cake resistance and compressibility during pressure filtration. (22nd April 2016) - Bourcier, D.; Féraud, J.P.; Colson, D.; Mandrick, K.; Ode, D.; Brackx, E.; Puel, F.
Abstract: The aim of this paper was to study cake filterability and compressibility as a function of the particle shape and particle size distribution (PSD). Different shapes and PSD of calcium carbonate and uranium oxalate particles covering the classical types encountered in industry (sphere, cube, needle and platelet) were obtained by precipitation. The size and shape factor distributions were measured using an image analysis system on SEM pictures. The cake filtration properties were measured in ideal monitored operating conditions, because of a miniaturised filtration cell set-up. The impact of the PSD and the shape were quantitatively assessed. These two solid features have an impact on cake resistance and compressibility, but not in the same way. The PSD has the strongest effect on cake resistance and compressibility. The particle shape is a decisive parameter for cake compressibility when the shape is far from the sphere. Both parameters need to be considered when working on the development of a filtration operation. Here, a practical model built following the Darcy law coupled with a new correlation for compressibility factor assessment is proposed. It gave satisfactory estimates of cake filterability and compressibility for the four shapes studied. Highlights: We develop a method to predict cake filtration behaviour with physical parameter. Compressibilty factor is linked with cake porosity and particle size distribution. The polydispersity is taken into account thanks to an additivity model.